Crystal structure, Raman spectra, infrared spectra and microwave dielectric properties of Li2Mg3Ti1-X(Mg1/3Ta2/3)XO6 (0 ≤ x ≤ 0.2) solid solution ceramics. (September 2018) - Pan, H.L.; Mao, Y.X.; Yang, Y.K.; Zhang, Y.W.; Wu, H.T.
Graphical abstract: Highlights: Microwave properties of εr  = 14.70, Q·f  = 200, 600 GHz and τf  = −11.83 ppm/°C were obtained. A small amount of (Mg1/3 Ta2/3 ) 4+ can obviously improve properties. Rietveld refinement and spectra were used to analyze properties. Relationships between intrinsic parameters and properties were established. Abstract: Li2 Mg3 Ti1-X (Mg1/3 Ta2/3 )X O6 (x = 0.00, 0.05, 0.10, 0.15, 0.20) solid solution ceramics were prepared by the conventional solid-state reaction method. Rietveld refinements, Raman spectra, infrared spectra, polarizability and bond energy were used to research the changes of microwave dielectric properties of these solid solutions. With the increase of x values from 0 to 0.2, dielectric constants ( εr ) gradually increased, which could be explained by the variations of the polarizability, infrared resonant modes and Raman vibration modes. The variations of the quality factor ( Q·f ) could be explained by the changes of the bond valences. The temperature coefficient of resonant frequency ( τƒ ) correlated with the bond energy of TiO bonds. A small quantity of (Mg1/3 Ta2/3 ) 4+ can obviously improve the microwave dielectric properties. Excellent microwave dielectric properties of εr  = 14.70, Q·f  = 200, 600 GHz and τf  = −11.83 ppm/°C were obtained for Li2 Mg3 Ti0.95 (Mg1/3 Ta2/3 )0.05 O6 ceramic sintered at 1550 °C.